Characteristics of Culturable Microbial Community in Rhizosphere/Non-rhizosphere Soil of Potentilla Fruticosa Population in Alpine Meadow Elevation Gradient - Liu, Minxia; Li, Bowen; Xu, Lu; Yu, Ruixin (Frontiers in Soil Science, 2021)
Potentilla fruticosa is a typical shrub of alpine meadows with canopy effects that can greatly influence soil fertility and microbiological parameters. Changes in rhizosphere microorganisms can reflect the response of these plants to environmental changes. This study aimed to examine the rhizosphere and non-rhizosphere of P. fruticosa on the amount of selected microorganisms and main environmental factors at different elevation gradients (3,000, 3,250, 3,500, 3,750, and 4,000 m). The results suggested that bacteria were predominant of the microbial soil community in the rhizosphere and non-rhizosphere, while fungi and actinomycetes represented the minority. With the increase of altitude, the total amount of microbial, bacteria, and actinomycetes in the rhizosphere and non-rhizosphere of P. fruticosa showed a downward trend, and microbial functional groups showed that the “hump shape” changed, but the fungi showed the opposite. Variance inflation factor (VIF) screening environmental factors and path analysis were obtained. In the rhizosphere soil, bacteria were affected by Soil organic carbon (SOC), and soil bulk density (SBD) became the main environmental limiting factor with the increase of altitude. The main environmental limiting factor of actinomycetes changed from SBD to Soil total (ST). In the non-rhizosphere soil, the bacteria and actinomycetes changed from ST to SOC and SBD, respectively. The main environmental limiting factor of the fungi was SOC in the rhizosphere and non-rhizosphere. Soil water content (SWC) was the main environmental determinant factor for all microbial groups, microbial functional groups were related to Soil total nitrogen (STN). Our results help to understand the relationship between nutrient cycling and the ecosystem function of alpine meadow plant soil microorganisms and provide theoretical support for alpine meadow ecosystem restoration, biodiversity protection, and the use of microbial resources.